Return or Remittances? Diaspora Economic Policies of Latin American and Caribbean States - Pedroza, Luicy (2019)
Explanations of why migrants return to their countries of origin  tend to focus on factors at micro and macro levels: from seeing it as individual  choice (e. g. neoclassical economics) or household strategy (e. g. new economics of labor migration), to seeing it as determined by structural  conditions of receiving or sending countries (e. g. economic cycles, wage  differentials, etc.). Yet we know very little about how states of origin combine  their policies towards emigrants to establish economic links with them,  from remittances to return. With an original dataset for Latin American  and Caribbean countries, we can provide an initial descriptive panorama  that highlights the choices that countries make in this regard. We compare  the return policies to other economic policies geared to emigrants. This  helps us in detecting return policies, which is often a neglected dimension  in comparative diaspora policy studies, as one among several that states of origin develop to achieve their economic strategies. Also, this first attempt at  descriptive analysis provides further paths to explore the causal links behind  diaspora policy development in the realm of economic policy.